Gyrodactylus anguillae and Vibrio vulnificus infections affecting cultured eel, Anguilla anguilla - Elgendy, Mamdouh Yousif; Kenawy, Amany Mohamed; Noor El-Deen, Ahmed E (Comunicata Scientiae, 2016)
Gyrodactylus anguillae and Vibrio vulnificus are pathogens of critical significance in anguilliculture. Both agents were involved in mortalities affecting earthen pond cultured European eel, Anguilla anguilla, in Egypt during the period extended from June to September 2014. Moribund eels showed excessive slimy mucus and haemorrhages on the external body surface. All investigated eels were parasitized with the monogenean, Gyrodactylus anguillae. Majority of specimens 93.3 % were concomitantly found to be infected with V. vulnificus. No other parasitic or bacterial infections were noticed in the investigated fish samples. V. vulnificus was detected in Gyrodactylus anguillae homogenates collected from diseased fish. Bacterial isolates were confirmed by polymerase chain reaction (PCR). G. anguillae were demonstrated in skin and gills histopathological sections. Varieties of circulatory, proliferative as well as degenerative changes were noticed in haemopoietic tissues. It was concluded that G. anguillae presumably enhanced eels vulnerability to V. vulnificus infections through providing portals of entry as well as acting as mechanical vectors.